Listening - White, Goodith (Oxford University Press, 1998)
A resource book of activities to prepare students for public examinations. Includes over 70 classroom activities ranging from raising awareness of individual sounds to full-scale listening projects. Emphasizes listening as a social and interactive skill. Helps learners to develop strategies to make sense of what they hear in English.